Streamlining Procedures for Board Consideration of The Fund's Emergency Financing During Exceptional Circumstances Involving A Pandemic. (Policy Papers; Policy Paper, 2020)
The COVID-19 pandemic has inflicted an unprecedented shock on the global economy and created an enormous demand for Fund resources. To accelerate processing and approval of members' requests in such circumstances, the paper proposes measures to expedite Board consideration and approval of requests for purchases and/or disbursements under the Rapid Financing Instrument and/or the Rapid Credit Facility, respectively, completion of reviews and requests for changes in access in existing arrangements, and requests for assistance under the Catastrophe Containment and Relief Trust (CCRT), by shortening the circulation period for Board documents. The paper also proposes extending the use of the shortened circulation period to selected Article IV consultations necessary for use of Fund resources during a global pandemic. Management will also streamline internal procedures to accelerate program processing and reduce the burden on the Fund's administrative capacity, and will seek the support of creditors to expedite the processing of financial transactions under COVID-19 emergency financing.